Analysis of fisheries resource access regulations in the Visayan sea, Philippines - Subade, Rodelio F.; Ventura, Brian; Fernandez, Pepito, Jr (Danyag :the UPV journal of humanities and social sciences, 2007)
"Fisheries Resource Access Regulations (FRAR) have been enshrined in the constitution and other national laws, aimed towards helping subsistence or municipal fishers improve their lot. Moreover, these national legislations have instituted the use of various mechanisms in implementing resource access regulations, generally categorized as individual fishing rights (JFR), common property rights/regime approach (CPR) and command and control schemes (C&C). Most of Northern Iloilo coastal municipalities are in more advanced stage of establishing their FRAR system compared to those from Northern Cebu, Northern Negros and Southern Masbate. In particular, Concepcion appears to have employed various FRAR mechanisms complemented by detailed municipal fishery ordinance and coastal resource management (CRM) plan, significant resource allotment (budget and patrol boats) for CRM and FRAR implementation. There is a need to translate into local implementing rules and regulations (IRR) the municipal ordinances for FRAR in order to provide clarity and effectivity in the practice of such schemes, such that the Visayan Sea coastal and fisheries resources will be utilized and conserved in a sustainable manner. Recommendations are provided to improve local fisheries resource access."